Structure theory and stable rank for C*-algebras of finite higher-rank graphs. Issue 4 (4th November 2021) - Pask, David; Sierakowski, Adam; Sims, Aidan
Abstract: We study the structure and compute the stable rank of $C^{*}$ -algebras of finite higher-rank graphs. We completely determine the stable rank of the $C^{*}$ -algebra when the $k$ -graph either contains no cycle with an entrance or is cofinal. We also determine exactly which finite, locally convex $k$ -graphs yield unital stably finite $C^{*}$ -algebras. We give several examples to illustrate our results.